FREE-RADICAL SCAVENGING ACTIVITY AND TOXICITY STUDY OF PSILOTUM NUDUM (L.) P. BEAUV., A LOWER PLANT ACCLIMATED IN NORTH BENIN x - Sangaré, Machioud; ATTAKPA, Eugène; ATEGBO, JEAN-MARC NOUNAGNON (My University, 2017)
ABSTRACT Both of higher and lower plants provide healthcare source for the population in rural and urban area in Benin and in the world. While some are explored for their biological properties, others remain less known. The aim of this study is to assess the phytochemical and toxicity properties of Psilotum nudum in rat. We used in vitro complexion and/ or precipitation reactions to detect the presence or absence of different groups of secondary metabolites in that Pteridophyte. The antiradical scavenging activity is shown by two different radical : DPPH and Hydroxyle radical. Blood biochemicals analysis before and after force-feeding (100 mg/kg of Body Weight (BW), 1000 mg/kg BW and 2500 mg/kg BW) and physical observation were used for toxicity assessement. Psilotum nudum contains different phytochemical compounds such as tanins and flavonoids likely responsible of the extract free radical scavenging activity. Changes observed in blood biochemical parameters [Urea, Creatinine, alanine aminotransferase (ALAT) and aspartate aminotransferase (ASAT)] after seven days of extract administration normalised after 30 days of observation. Upto this stage of our research, aqueous extract of P. nudum should be taken with caution.
Keywords: KEYWORDS: Psilotum nudum -scavenging activity-toxicity-Benin